Removal of alkylthiols from gold surface : molecular dynamics simulations in density functional theory - Kaappa, Sami (2015)
Self-assembled monolayers (SAMs) are systems of organic compounds adsorbed onto metal or silicon, forming a dense cover on top of the substrate; the most studied system of SAMs consists of alkylthiols on gold surface. In 2012, Liao et al. found out, as a side-product of their chemical lift-off lithography research, that when the thiol cover was pulled off the gold surface, a layer of gold was also removed from the substrate. In our study, this process was simulated using density functional theory (DFT) within projector augmented-wave (PAW) method to examine the dynamics at the interface of gold and the thiol cover. According to our results, acquired using the linear combination of atomic orbitals (LCAO) method and the PBE functional, about half of the top layer of gold is removed from the surface by the thiols. Both planar Au(111) surface and a surface with a terrace, Au(332), were examined and they showed similar behavior during the process. As this kind of calculations have not been performed before, some parameter tests including the pulling speed and the Langevin friction parameter tests were run. I also performed some calculations considering the optimal geometries and energetics of different alkylthiols and ensured that the LCAO method is justified in the dynamics simulations; the results were in agreement with the literature values. This study sheds light to the physical and chemical phenomena at the interface of gold surface and alkylthiol monolayers and builds a base for further investigations on the subject.